2019
DOI: 10.1371/journal.pone.0227251
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluations of screening strategies for the early detection of colorectal cancer in the average-risk population: A systematic literature review

Abstract: BackgroundColorectal cancer (CRC) screening has proven effective in reducing CRC mortality. This study aimed to systematically review, and evaluate the reporting quality, of the economic evidence regarding CRC screening in average-risk individuals.MethodsDatabases searched included Medline, EMBASE, National Health Service Economic Evaluation, Database of Abstracts of Reviews of Effects, Cost-Effectiveness Analysis registry, EconLit, and Health Technology Assessment database. Eligible studies were cost-effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 63 publications
0
17
0
1
Order By: Relevance
“…Many studies have found that CRC screening modalities are cost-effective. The screening methods considered in these studies were iFOBT (70%), colonoscopy (67%), gFOBT (42%), and sigmoidoscopy (30%), but they were not conclusive on which screening method is the best to adopt for population-based CRC screening programs [78]. While the study by Jahn et al [79] concluded that the most effective CRC screening method was iFOBT annually or colonoscopy every 10 years, the gFOBT was less effective and more expensive than the iFOBT.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that CRC screening modalities are cost-effective. The screening methods considered in these studies were iFOBT (70%), colonoscopy (67%), gFOBT (42%), and sigmoidoscopy (30%), but they were not conclusive on which screening method is the best to adopt for population-based CRC screening programs [78]. While the study by Jahn et al [79] concluded that the most effective CRC screening method was iFOBT annually or colonoscopy every 10 years, the gFOBT was less effective and more expensive than the iFOBT.…”
Section: Discussionmentioning
confidence: 99%
“…7,26,27 However, it is not clear which screening strategy is preferable for a populationbased CRC screening programme, as costs of screening, screening adherence, test sensitivity, and costs of CRC treatment have a substantial impact on overall costeffectiveness and are highly dependent on country settings. 28 For example in a previous economic evaluation, Arrospide et al 26 found that, in the first years of the CRC FIT screening programme in the Basque country (64.3% screening adherence), e69.2 million were necessary (on average) to annually fund the programme. In our budget analysis, we found that in Hungary the current FIT screening programme would need from e14 to e20 million of annual funds (Supplementary Table 4) during its first years assuming that 20% of the individuals in the target population participated in screening.…”
Section: Discussionmentioning
confidence: 99%
“…Colonoscopy is the only invasive procedure with the dual capability of optically screen the entire colonic mucosa and perform a polypectomy procedure (Brenner et al, 2014). Interestingly, the removal of polyps is associated with a reduction of 60% of deaths (Fras et al, 2018;Mendivil et al, 2019). Polyps are small clumps of cells that grow on the colonic surface and may eventually become cancer (Gorgun et al, 2016;Ponugoti et al, 2017), thus their removal is an essential procedure able to stop this process.…”
Section: Introductionmentioning
confidence: 99%